Experimental and Theoretical Analysis of Active Charge Accumulator for Water Hydraulics System - Futoshi Yoshida; Shouichiro Iio; Kenji Ito; Ato Kitagawa (IEEE Access, 2017)
The active charge accumulator (ACA) is a pressure converter device in a water-hydraulic system that is able to increase and decrease pressure without using a pressure-regulating valve. The basic characteristics of ACAs, however, have not yet been sufficiently revealed. In this paper, we experimentally examined the basic characteristics of ACAs with focus placed on how ACAs reduce pressure. This examination has revealed that the piston stroke of ACAs depends on the load flow rate as well as the valve switching timing. We theoretically analyzed these phenomena using a mathematical model. With an analytic model built taking into consideration the compressibility of the working fluid, valve performance level, and other elements, we made a comparison between the analytic and experimental results to verify the validity of our analysis. This comparison revealed that the pressure waveforms in the low-pressure and pressure-conversion sections obtained through the analysis agreed with those obtained through the experiments, indicating that the analytic model was valid.